2019
DOI: 10.1177/0972262919840228
|View full text |Cite
|
Sign up to set email alerts
|

A Mediation Effect of Job Satisfaction and Affective Commitment in Relationship Between Passion and Work Intentions after Retirement

Abstract: The aim of this study is to identify an intention towards work after retirement. This article examines the multilevel sequential mediating role of job satisfaction and affective commitment in the relationship between passion for work and intention towards work. This study has used 310 respondents retired from government jobs and data are collected through a well-administered questionnaire. Smart partial least square-structural equation modelling (SmartPLS-SEM) was used to analyse data. Path analysis of the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
3
8
0
Order By: Relevance
“…The relationship between the mediating variable (harmonious passion for work) and the dependent variable (work intentions) was significant, although negative, thus causing a negative mediation of the harmonious passion for work in the relationship between the servant leadership and the intentions of work. Results consistent with these findings were also observed in a study in which a negative relationship was found between passion for work and other types of work intentions (Tarkar et al, 2019).…”
Section: Limitations and Future Studiessupporting
confidence: 87%
“…The relationship between the mediating variable (harmonious passion for work) and the dependent variable (work intentions) was significant, although negative, thus causing a negative mediation of the harmonious passion for work in the relationship between the servant leadership and the intentions of work. Results consistent with these findings were also observed in a study in which a negative relationship was found between passion for work and other types of work intentions (Tarkar et al, 2019).…”
Section: Limitations and Future Studiessupporting
confidence: 87%
“…Cheasakul & Varma (2016) stated a relationship between passion, empowerment, and organizational commitment. This is supported by Tarkar et al (2019)'s research, which reported that passion significantly affects job satisfaction, affective commitment, and intention towards work. Tladinyane et al (2016) also found a positive relationship between career adaptability and employee engagement.…”
Section: Introductionsupporting
confidence: 53%
“…Moreover, employees’ satisfaction with their work is strongly related to their commitment to the organization ( Boles et al, 2007 ). Employee’s commitment is an important variable because a high level of commitment will bring beneficial outcomes to the organization ( Tarkar et al, 2019 ). Empirical studies have found that the affective commitment [i.e., one of the three components of organizational commitment identified by Meyer and Allen (1991) ] played a moderating role in the relationship between triggers of stress and job strain ( Irving and Coleman, 2003 ).…”
Section: Introductionmentioning
confidence: 99%